Perbandingan Ideal Prima Pada Gelanggang Polinomial Bilangan Bulat dan Gelanggang Polinomial Bilangan Bulat Modulo - Daisyah Alifian Fatahilah (Mathematics Department, Faculty of Mathematics and Sciences Unisda Lamongan, 2022)
A ring can be formed into a new ring, called a polynomial ring or what is often called an ring. For is a polynomial ring which is often referred to as an integer polynomial ring modulo n. The polynomial ring of R is the set of all polynomials with constants in the form of elements in . In 2019 Maulana et al discussed the prime ideal properties of Gaussian integers. In this article, we will give a comparison of the prime ideal properties in the modulo integer polynomial ring with the integer polynomial ring, where if the prime ideal in integers is not necessarily prime ideal in the modulo integer ring.